Metode Langsung (Al-Tarīqah Al-Mubāsyarah) dan Strategi Pembelajarannya - Sitti Aisyah Chalik (Shaut al Arabiyyah, 2020)
Direct means straight to the point. Direct method or straight to the point method is the way in presenting Arabic where the teacher directly uses the language ( Arabic) as the language in giving instruction , without using students‟ mother tongue . If there is a word is difficult to understand by the students, teachers can interpret that word by using props, demonstrating, describing and etc. This method is based on the understanding that teaching foreign language subject is not the same as teaching the science subject. If in the Learning science, the students are required to memorize certain formulas, think and remember, in language teaching, students or pupil are trained to practice directly spelling certain words or sentences. It is same when we consider a mother in teaching language to her childrens, she practices the language by herself directly , lead her child to pronounce the word by -word, sentence by-sentence, and her children will repeat what she spell in funny way. In principle, Direct method is really important in teaching Arabic, because through this method students can practice their speaking skills directly without using their mother tongue (the language of their scope). Although in the first time it seems difficult for students to duplicate it, but this method finally so interesting for them.